A Study on Development Schemes of Rural India - Himanshu Pandey; Prof. Vijay Kumar Agarwal (International Journal of Engineering and Management Research, 2022)
Rural development is gaining global attention, especially among developing nations. It has great importance for a country such as India. It refers to the development of rural economies, which are experiencing serious poverty issues, and aims to develop their productivity. In addition, the report stresses the importance of addressing different pressing issues of village economies that impede growth and improve these areas. The Indian government has launched several schemes to develop rural areas. A few of the major problems in rural India are the lack of housing, the lack of infrastructure in villages and towns to connect villages with all-weather roads, and the lack of employment opportunities. The purpose of this paper is to analyze the government of India has announced the Pradhan Mantri Awaas Yoiana Gramin scheme to provide homes, Pradhanmantri Gram Sadak Yojana to build roads and To provide rural people with employment opportunities, the Mahatma Gandhi National Rural Employment Guarantee Act 2005 was passed. In this study, we discover what the role of these schemes is in India's rural development, as well as how they are progressing at present.